A Scalable and Privacy-Enhanced Federated Learning Framework with Adaptive Trade-offs Between Communication Efficiency, Privacy Guarantees, and Model Performance in Non-IID Environments - Milad Rahmati; Nima Rahmati (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2025)
Federated learning (FL) has become a promising paradigm for collaborative machine learning that preserves the privacy of distributed data sources. However, implementing privacy-preserving federated learning (PPFL) in real-world settings poses several critical challenges, particularly in balancing communication efficiency, strong privacy guarantees, and reliable model performance. These issues are further exacerbated in non-IID (non-independent and identically distributed) environments, which are common in decentralized data scenarios. This study introduces a scalable framework for PPFL that incorporates an adaptive mechanism to optimize trade-offs among communication, privacy, and performance, tailored to dynamic, resource-constrained settings. The proposed framework integrates advanced differential privacy techniques with efficient communication strategies and employs robust aggregation algorithms to address data heterogeneity. Analytical evaluations highlight the scalability and effectiveness of the approach, while experimental validations demonstrate its advantages in terms of privacy-accuracy trade-offs across diverse datasets, including applications in healthcare and IoT. This work contributes to enhancing the practicality of FL systems by demonstrating a 6.5% accuracy improvement on CIFAR-10 in non-IID settings, maintaining 87.2% accuracy at a strict privacy budget of ε=1.0, and reducing communication overhead by 40% compared to baselines, addressing key barriers to deployment and setting a foundation for future research in dynamic, privacy-preserving machine learning systems. Keywords: Adaptive algorithms; Data heterogeneity; Differential privacy; Distributed systems; Scalability.   Abstrak Pembelajaran terfederasi (Federated learning) telah menjadi paradigma yang menjanjikan untuk pembelajaran mesin kolaboratif yang menjaga privasi sumber data terdistribusi. Namun, penerapan pembelajaran terfederasi yang menjaga privasi (PPFL) dalam dunia nyata menghadapi beberapa tantangan kritis, terutama dalam mencapai keseimbangan antara efisiensi komunikasi, jaminan privasi yang kuat, dan kinerja model yang andal. Masalah-masalah ini semakin diperparah dalam lingkungan non-IID (non-independen dan terdistribusi identik), yang umum terjadi dalam skenario data terdesentralisasi. Artikel ini memperkenalkan kerangka kerja yang skalabel untuk PPFL yang menggabungkan mekanisme adaptif untuk mengoptimalkan trade-off antara komunikasi, privasi, dan kinerja, yang disesuaikan dengan pengaturan dinamis dan terbatas sumber daya. Kerangka kerja yang diusulkan mengintegrasikan teknik privasi diferensial tingkat lanjut dengan strategi komunikasi yang efisien dan menggunakan algoritma agregasi yang tangguh untuk mengatasi heterogenitas data. Evaluasi analitis menyoroti skalabilitas dan efektivitas pendekatan ini, sementara validasi eksperimental menunjukkan keunggulannya dalam hal trade-off privasi-akurasi di berbagai set data, termasuk aplikasi di bidang kesehatan dan IoT. Hal ini berkontribusi dalam meningkatkan kepraktisan sistem FL dengan menunjukkan peningkatan akurasi sebesar 6,5% pada CIFAR-10 dalam pengaturan non-IID, mempertahankan akurasi sebesar 87,2% pada anggaran privasi yang ketat sebesar ε=1,0, dan mengurangi overhead komunikasi sebesar 40% dibandingkan dengan model dasarnya, mengatasi hambatan utama untuk penerapan dan menetapkan landasan untuk penelitian selanjutnya dalam sistem pembelajaran mesin yang dinamis dan menjaga privasi. Kata Kunci: Algoritma adaptif; Heterogenitas data; Privasi diferensial; Sistem terdistribusi; Skalabilitas. 2020MSC: 68T07, 68W15.